Public Procurement and the Private Business Sector : Evidence from Firm-Level Data - Ghossein, Tania; Islam, Asif Mohammed; Saliola, Federica (World Bank, Washington, DC, 2018)
The quality of the public procurement system of an economy can have far-reaching effects on the private sector. This paper empirically explores several of these effects using two rich data sets. An overall indicator of public procurement quality is created from the World Bank’s Benchmarking Public Procurement project that is then combined with firm-level data from the World Bank Enterprise Surveys. The analysis includes more than 59,000 firms spanning more than 109 economies. The paper finds that firms in economies with good public procurement systems are more likely to participate in public procurement, face lower losses from shipping to domestic markets, and experience lower incidence of bribery than economies with poor public procurement systems. Similarly, better public procurement systems are positively correlated with more engagement in innovation, research and development, international certification, foreign technology adoption, and online connectivity.